Quick coherence technique facilitating commercial pilots’ psychophysiological resilience to the impact of COVID-19 - Li, Wen-Chin; Zhang, Jingyi; Braithwaite, Graham; Kearney, Peter (Taylor and Francis, 2022)
This study investigates the effect of quick coherence technique (QCT) on commercial pilots’ resilience to the unprecedented impact of a pandemic. Eighteen commercial pilots voluntarily participated in a 2-day training course on QCT followed by 2 months of self-regulated QCT practicing during controlled rest in the flight deck and day-to day life. There are subjective and objective assessments to evaluate the effects of QCT on commercial pilots’ psychophysiological resilience. Results demonstrated that QCT training can significantly increase pilots’ psychophysiological resilience thereby improving their mental/physical health, cognitive functions, emotional stability and wellness on both subjective (PSS & AWSA) and objective measures (coherence scores). Moreover, pilots who continued practicing self-regulated QCT gained the maximum benefits. Current research has identified great potential to enhance pilots’ mental/physical health via QCT training. Operators can develop peer support programs for pilots to increase resilience and maintain mental and physical health using the QCT technique. Practitioner summary: QCT breathing has been proven to increase commercial pilots’ resilience by moderating psychophysiological coherence, strengthening mental/physical capacity and sustaining positive emotions to deal with the challenges both on the flight deck and in everyday life.
Keywords: Aviation safety; biofeedback training; controlled rest; psychophysiological resilience; quick coherence technique